2021
DOI: 10.1177/1941738120986803
|View full text |Cite
|
Sign up to set email alerts
|

Effects of 8 Weeks of Balance Training, Virtual Reality Training, and Combined Exercise on Lower Limb Muscle Strength, Balance, and Functional Mobility Among Older Men: A Randomized Controlled Trial

Abstract: Background: Poor muscle strength, balance, and functional mobility have predicted falls in older adults. Fall prevention guidelines recommend highly challenging balance training modes to decrease falls; however, it is unclear whether certain modes are more effective. The purpose of this study was to determine whether traditional balance training (BT), virtual reality balance training (VR), or combined exercise (MIX) relative to a waitlist control group (CON) would provoke greater improvements in strength, bala… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
93
1
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 71 publications
(97 citation statements)
references
References 56 publications
1
93
1
2
Order By: Relevance
“…Several studies have previously confirmed the beneficial effects of exergames on postural control among older adults [ 22 , 23 , 26 , 29 , 31 - 35 ]. This usability study shows that a simple Kinect game–based balance training might be beneficial for older women by improving balance in the ML direction.…”
Section: Discussionmentioning
confidence: 96%
See 3 more Smart Citations
“…Several studies have previously confirmed the beneficial effects of exergames on postural control among older adults [ 22 , 23 , 26 , 29 , 31 - 35 ]. This usability study shows that a simple Kinect game–based balance training might be beneficial for older women by improving balance in the ML direction.…”
Section: Discussionmentioning
confidence: 96%
“…The m-CTSIB test was initially developed by Shumway-Cook and Horak [ 45 ] to differentiate sensory (somatosensory, visual, and vestibular) inputs involved in postural stability during a steady-state balance assessment, and it explored balance on various surface types, with and without vision, using 4 sensory conditions: (1) firm surface, eyes open; (2) firm surface, eyes closed; (3) foam surface, eyes open; and (4) foam surface, eyes closed. The results provided by the Balance Master 6.0’s software package gave 3 measurements of COG (3 × 10 s) in the anteroposterior (AP) and ML directions [ 35 ]. Based on a previous study [ 43 ] with elderly females in all 4 sensory conditions, this test had good to excellent reliability of ML (intraclass correlation coefficient 0.88-0.93) and AP path length (intraclass correlation coefficient 0.85-0.90).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…More than 70% of falls in older adults take place during gait [9]. For a normal gait, many systems are required, such as sensation and coordination, lower limb and core muscle strength, balance, and function in an integrated fashion [10,11]. A decrease in gait speed with an increase in age can be viewed as an adaptation to compensate for declining sensory-motor function in order to prevent the occurrence of falls.…”
Section: Introductionmentioning
confidence: 99%